Antiepileptic effect of olanzapine in epilepsy patients with atypical depressive comorbidity. Issue 3 (18th July 2018) - Qiu, Xiangmiao; Zingano, Bianca; He, Shixu; Zhu, Xi; Peng, Anjiao; Duan, Jianan; Wolf, Peter; Chen, Lei
ABSTRACT: Depression is relatively common among patients with epilepsy, but often with predominant atypical symptoms. Some antiepileptic drugs show positive psychotropic effects, but these are not always sufficient to stabilize mood in epilepsy patients. Antidepressants are recommended to treat atypical depression but are not always effective and present a certain risk of seizure provocation. Thus, new treatment options are welcome. Here, we describe three cases of refractory epilepsy with atypical depression in which olanzapine, contrary to its earlier reported proconvulsant effect, showed excellent antidepressant action and resulted in seizure control. Possible mechanisms of this action are discussed.